2020
DOI: 10.1542/peds.2020-0715
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Release Assays for Tuberculosis Infection Diagnosis in Refugees <5 Years Old

Abstract: BACKGROUND: New guidelines support using interferon-g release assays (IGRAs) in children $2 years for diagnosis of latent tuberculosis infection (LTBI). However, lack of experience in young children and concern that IGRAs are less sensitive than tuberculin skin tests (TSTs) limit their use. Our aim was to identify active tuberculosis (TB) cases among high risk children ,5 years and tested for LTBI with an IGRA. METHODS: . Retrospective review of domestic TB screening data from California's Refugee Health Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Different studies had different conclusions regarding the value of IGRAs and the TST for diagnosing LTBI. A cohort study of BCG-vaccinated children younger than 5 years showed that there was a high discordance (12.3%) between IGRAs and the TST, mostly TST+/IGRA− [ 40 ]; another study showed that for high-risk children aged 2–5 years old, IGRAs’ positivity was lower than that of the TST [ 41 ]. None of the TST+/IGRA− children developed into ATBI during the follow-up even without prophylactic treatment, demonstrating the false positivity of the TST that came from the cross-reaction with BCG [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies had different conclusions regarding the value of IGRAs and the TST for diagnosing LTBI. A cohort study of BCG-vaccinated children younger than 5 years showed that there was a high discordance (12.3%) between IGRAs and the TST, mostly TST+/IGRA− [ 40 ]; another study showed that for high-risk children aged 2–5 years old, IGRAs’ positivity was lower than that of the TST [ 41 ]. None of the TST+/IGRA− children developed into ATBI during the follow-up even without prophylactic treatment, demonstrating the false positivity of the TST that came from the cross-reaction with BCG [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of BCG-vaccinated children younger than 5 years showed that there was a high discordance (12.3%) between IGRAs and the TST, mostly TST+/IGRA− [ 40 ]; another study showed that for high-risk children aged 2–5 years old, IGRAs’ positivity was lower than that of the TST [ 41 ]. None of the TST+/IGRA− children developed into ATBI during the follow-up even without prophylactic treatment, demonstrating the false positivity of the TST that came from the cross-reaction with BCG [ 40 , 41 , 42 ]. Using the TST as a standard, a meta-analysis showed that IGRAs had higher sensitivity and specificity, with the pooled sensitivity and specificity of ELISA being 84.1 and 89.5%, respectively, and the pooled sensitivity and specificity of ELISPOT were 93.1 and 76.7%, respectively [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…27 Studies included children with different population features also support the use of IGRAs for children. [28][29][30] On the contrary, the Canadian Thoracic Society suspected that IGRA performed worse in young children than in adults. 31 However, studies of meta-analysis confirmed that IGRA was more specific in low-risk, BCG-vaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…While for children aged ≥5–18 years, IGRAs had greater sensitivity than TST. Interestingly, several studies have shown that none of the untreated children with negative IGRA progressed to ATB even with discordant test results TST + /IGRA − , suggesting that clinicians can rely on IGRA negative results as TST might be causing overdiagnosis and unnecessary treatment [ 77 , 78 ]. Although repeated IGRA testing was required for indeterminate results, the percentage is lower than those who fail to return for TST reads [ 77 ].…”
Section: Screening Tests For Tbimentioning
confidence: 99%
“…In mycobacterial infections, IFN-γ released by CD4 + T cells is essential for host survival and enhances both CD4 + and CD8 + T cell activities [ 129 ]. However, false-negative IGRA results were detected in patients with TB infection with advanced age [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , …”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%